Plant-scale performance and economic trade-offs of polyamide thin-film composite vs. cellulose triacetate hollow fiber membranes for seawater desalination - Mosaab Alghamdi; Ali M. Alasmari; Abdulaali Alharbi; Dilshad Mundampra; Zahir Ali Khan; Muhammed Rasik Abdurahiman; Hamed Alshamrani; Omar Alghamdi; Thomas Altmann; Ratul Das (Desalination, 2026)

Making waves: Rethinking antiscalants in seawater desalination – Balancing scaling control, biofouling risk, and ecological consequences - Graciela Gonzalez-Gil; Marian Castrillón-Tobón; Maria Camila Albarracin Ruiz; Ratul Das; Thomas Altmann; Johannes S. Vrouwenvelder (Water Research, 2026)

Evaluation of multimedia filtration as reverse osmosis pretreatment: Removal of particles, bacteria and organics - Yasmeen Nadreen; Johannes Vrouwenvelder; Thomas Altmann; Ratul Das; Graciela Gonzalez-Gil (Water Research, 2026)

A multi-class deep learning segmentation approach for automated analysis of axial and lateral roots in barley plants - Narendra Narisetti; Kerstin Neumann; Thomas Altmann; Frieder Stolzenburg; Nicolaus von Wirén; Ricardo Fabiano Giehl; Evgeny Gladilin (Computers and Electronics in Agriculture, 2026)

On the discrepancy between nominal and effective charge density of polyamide reverse osmosis membranes - Bastiaan Blankert; Fernan D. Martinez; Ratul Das; Thomas Altmann; Johannes S. Vrouwenvelder; Cristian Picioreanu (Desalination, 2024)

Effectiveness of ceramic ultrafiltration as pretreatment for seawater reverse osmosis - Thomas Altmann; Ana Rousseva; Johannes Vrouwenvelder; Michael Shaw; Ratul Das (Desalination, 2023)

The microbial growth potential of antiscalants used in seawater desalination - Ghadeer Hasanin; Ana Maria Mosquera; Abdul-Hamid Emwas; Thomas Altmann; Ratul Das; Paulus J. Buijs; Johannes S. Vrouwenvelder; Graciela Gonzalez-Gil (Water Research, 2023)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Multi-omics-based prediction of hybrid performance in canola - Dominic Knoch; Christian R. Werner; Rhonda C. Meyer; David Riewe; Amine Abbadi; Sophie Lücke; Rod J. Snowdon; Thomas Altmann (Theoretical and Applied Genetics, 2021)
Key message Complementing or replacing genetic markers with transcriptomic data and use of reproducing kernel Hilbert space regression based on Gaussian kernels increases hybrid prediction accuracies for complex agronomic traits in canola . In plant breeding, hybrids gained particular importance due to heterosis, the superior performance of offspring compared to their inbred parents. Since the development of new top performing hybrids requires labour-intensive and costly breeding programmes, including testing of large numbers of experimental hybrids, the prediction of hybrid performance is of utmost interest to plant breeders. In this study, we tested the effectiveness of hybrid prediction models in spring-type oilseed rape ( Brassica napus L./canola) employing different omics profiles, individually and in combination. To this end, a population of 950 F 1 hybrids was evaluated for seed yield and six other agronomically relevant traits in commercial field trials at several locations throughout Europe. A subset of these hybrids was also evaluated in a climatized glasshouse regarding early biomass production. For each of the 477 parental rapeseed lines, 13,201 single nucleotide polymorphisms (SNPs), 154 primary metabolites, and 19,479 transcripts were determined and used as predictive variables. Both, SNP markers and transcripts, effectively predict hybrid performance using (genomic) best linear unbiased prediction models (gBLUP). Compared to models using pure genetic markers, models incorporating transcriptome data resulted in significantly higher prediction accuracies for five out of seven agronomic traits, indicating that transcripts carry important information beyond genomic data. Notably, reproducing kernel Hilbert space regression based on Gaussian kernels significantly exceeded the predictive abilities of gBLUP models for six of the seven agronomic traits, demonstrating its potential for implementation in future canola breeding programmes.

Seed-produced anti-globulin VHH-Fc antibodies retrieve globulin precursors in the insoluble fraction and modulate the Arabidopsis thaliana seed subcellular morphology - Thomas De Meyer; Elsa Arcalis; Stanislav Melnik; Katrien Maleux; Jonah Nolf; Friedrich Altmann; Ann Depicker; Eva Stöger (Plant Molecular Biology, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Genetic diversity for nitrogen use efficiency in Arabidopsis thaliana - Rhonda C. Meyer; Corina Gryczka; Cathleen Neitsch; Margarete Müller; Andrea Bräutigam; Armin Schlereth; Hardy Schön; Kathleen Weigelt-Fischer; Thomas Altmann (Planta, 2019)

Plant species and organ influence the structure and subcellular localization of recombinant glycoproteins - Elsa Arcalis; Johannes Stadlmann; Thomas Rademacher; Sylvain Marcel; Markus Sack; Friedrich Altmann; Eva Stoger (Plant Molecular Biology, 2013)

Enriched partial correlations in genome-wide gene expression profiles of hybrids (A. thaliana): a systems biological approach towards the molecular basis of heterosis - Sandra Andorf; Joachim Selbig; Thomas Altmann; Kathrin Poos; Hanna Witucka-Wall; Dirk Repsilber (Theoretical and Applied Genetics, 2010)

Prediction of hybrid biomass in Arabidopsis thaliana by selected parental SNP and metabolic markers - Matthias Steinfath; Tanja Gärtner; Jan Lisec; Rhonda C. Meyer; Thomas Altmann; Lothar Willmitzer; Joachim Selbig (Theoretical and Applied Genetics, 2010)

QTL analysis of early stage heterosis for biomass in Arabidopsis - Rhonda Christiane Meyer; Barbara Kusterer; Jan Lisec; Matthias Steinfath; Martina Becher; Hanno Scharr; Albrecht E. Melchinger; Joachim Selbig; Ulrich Schurr; Lothar Willmitzer; Thomas Altmann (Theoretical and Applied Genetics, 2010)

Determination of the overall migration from silicone baking moulds into simulants and food using 1 H-NMR techniques - Ruediger Helling; Anja Mieth; Stefan Altmann; Thomas Joachim Simat (Food Additives & Contaminants: Part A, 2009)

Segregation distortion in Arabidopsis C24/Col-0 and Col-0/C24 recombinant inbred line populations is due to reduced fertility caused by epistatic interaction of two loci - Ottó Törjék; Hanna Witucka-Wall; Rhonda C. Meyer; Maria von Korff; Barbara Kusterer; Carsten Rautengarten; Thomas Altmann (Theoretical and Applied Genetics, 2006)

From chemosensory thresholds to whole body exposures—experimental approaches evaluating chemosensory effects of chemicals - Christoph van Thriel; Michael Schäper; Ernst Kiesswetter; Stefan Kleinbeck; Stephanie Juran; Meinolf Blaszkewicz; Hajo-Hennig Fricke; Lilo Altmann; Hans Berresheim; Thomas Brüning (International Archives of Occupational and Environmental Health, 2006)

Evidence for a large-scale population structure of Arabidopsis thaliana from genome-wide single nucleotide polymorphism markers - Karl J. Schmid; Ottó Törjék; Rhonda Meyer; Heike Schmuths; Matthias H. Hoffmann; Thomas Altmann (Theoretical and Applied Genetics, 2006)

Changes in gene expression in response to altered SHL transcript levels - Carsten Müssig; Thomas Altmann (Plant Molecular Biology, 2003)

Genomic Brassinosteroid Effects - Carsten Mssig; Thomas Altmann (Journal of Plant Growth Regulation, 2003)

Phosphate acquisition heterosis in Arabidopsis thaliana: a morphological and physiological analysis - Ram A. Narang; Thomas Altmann (Plant and Soil, 2001)

12-Oxophytodienoate reductase 3 (OPR3) is the isoenzyme involved in jasmonate biosynthesis - Florian Schaller; Christian Biesgen; Carsten Müssig; Thomas Altmann; Elmar W. Weiler (Planta, 2000)

Molecular physiology of brassinosteroids revealed by the analysis of mutants - Thomas Altmann (Planta, 1999)